Chiral arene ruthenium complexes .2. A diastereoselective route to [(eta(6)-benzyl alcohol)(COD)Ru] complexes - Bodes, Gregor; Heinemann, Frank Wilhelm; Zenneck, Ulrich (Chemische Berichte, 1997)
Two preparative routes are reported that give access to the racemic series of planar chiral [(arene)(COD)Ru] derivatives containing eta(6)-bonded o-tolyl ketone or aldehyde arene units. The ketone and aldehyde functions of these have subsequently been reduced by nBuLi and PhLi, respectively. Hydrolysis converts the initially formed lithium salts into diastereomeric benzyl alcohol complexes in high yields. The formation of the new stereogenic centre is diastereoselective (88% de) for the aldehyde and diastereospecific for the ketone (de > 99%). Due to a sterically overcrowded situation, the rotation of the chiral side chain of [(COD)(eta(6)-o-tolyl-tert-butylphenylmethanol) Ru] (7) is hindered, as is the rotation of the phenyl and tert-butyl substituents. As a consequence, the hydroxyl group is fixed at a position close to the metal both in solution and in the solid state.
Keywords: arene complexes; ruthenium; diastereoselective; reduction